Porosity formation during atmospheric ice accretion: measurements using micro-computed tomography - Velandia, Juan S.; Diener, Alexander; Bansmer, Stephan E. (Journal of Glaciology, 2021)
Atmospheric ice accretion results from the exposure of technical equipment or facilities to cold and humid environments. Supercooled droplets in a cloud can impact an airplane's surface and quickly form an ice layer. The presence of air pockets in such a layer is well known and explains the white appearance of some of the accretions. However, estimation of its porosity values and studies on the pore formation mechanics remain limited. In this study, we performed tests in an icing wind tunnel and scans with micro-computed tomography to address these issues. Here, we show that the accretion has closed porosity below 1%, which is mostly produced by the interaction between a spray-like impact on the water surface. The insights we provide here are important to improve ice accretion modelling techniques and establish a different approach to address the interaction between the cloud and the surfaces exposed to atmospheric icing.